Pengaruh Profitabilitas Terhadap Harga Saham Pada Perusahaan Konsumsi Yang Terdaftar Di BEI 2020-2022 - Muhammad Firdaus Saputra; Steven Wilsen; Ratih Kusumastuti (Jurnal Mutiara Ilmu Akuntansi, 2023)
This study aims to see the effect of profitability on stock prices, especially for consumer companies listed on the Indonesia Stock Exchange in 2020-2022. This study uses the method of regression analysis to examine the effect of profitability on stock prices in consumer companies listed on the IDX. The independent variables used include return on assets (X1) and return on equality (X2) with the dependent variable being stock prices (Y). Where the results of this study indicate that ROA has a negative and insignificant effect on stock prices in consumer companies listed on the Indonesia Stock Exchange. Other results show that ROE has a negative and insignificant effect on stock prices in consumer companies listed on the Indonesia Stock Exchange.